Skin-friendly antibacterial fiber and preparation method thereof
Modified polyester was prepared by reacting modified copper/zinc oxide nanoparticles with polysiloxane, which solved the problem of poor hygroscopicity of polyester fibers and prepared fibers with good skin-friendly and antibacterial properties.
Patent Information
- Application Number
- CN202511068458.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-09-12
AI Technical Summary
The poor hygroscopicity of polyester fiber limits its application.
Modified copper/zinc oxide nanoparticles are prepared and reacted with polysiloxane to generate modified polyester, which is then melt-extruded, granulated, and spun with the modified copper/zinc oxide nanoparticles through a twin-screw extruder to prepare skin-friendly and antibacterial fibers.
The hydrophilicity and antibacterial properties of the fiber are improved, the moisture regain is enhanced, and a good antibacterial effect is achieved.
Smart Images

Figure BDA0005527585690000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fiber fabrics, in particular to a skin-friendly antibacterial fiber and a preparation method thereof. Background Art
[0002] Polyester fiber, also known as "terylene," is a high-molecular-weight polymer produced by melt-condensing terephthalic acid and ethylene glycol into polyester, followed by melt spinning. It is currently the world's largest synthetic fiber. Fabrics made from polyester fiber exhibit excellent wrinkle resistance and shape retention, along with superior mechanical properties, durability, and a wide range of applications.
[0003] However, polyester fibers have a regular macromolecular chain structure, high crystallinity and orientation, but lack hydrophilic groups in the macromolecular chain, resulting in poor hygroscopicity and limiting their application. The skin-friendly antibacterial fiber prepared by the present invention has excellent antibacterial properties and moisture regain, and has broad market prospects. Summary of the Invention
[0004] The purpose of the present invention is to provide a skin-friendly antibacterial fiber and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] Disclosed is a skin-friendly antibacterial fiber. The skin-friendly antibacterial fiber is prepared by reacting zinc nitrate and copper nitrate and then calcining to obtain copper / zinc oxide nanoparticles; the copper / zinc oxide nanoparticles are activated by N,N'-carbonyldiimidazole and then reacted with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to obtain modified copper / zinc oxide nanoparticles; octamethylcyclotetrasiloxane is reacted with 3-chloropropylmethyldimethoxysilane and then with hydroxypropyl silicone oil to obtain polysiloxane; 1,3-propylene glycol, dimethyl terephthalate and polytetramethylene ether glycol are reacted to obtain prepolyester; the prepolyester is reacted with polysiloxane to obtain modified polyester; and the modified polyester and modified copper / zinc oxide nanoparticles are melt-extruded through a twin-screw extruder, granulated and spun.
[0007] A method for preparing skin-friendly antibacterial fiber comprises the following steps:
[0008] (1) zinc nitrate and copper nitrate are mixed in a molar ratio of 20:1, deionized water (3 to 5 times the mass of zinc nitrate) and citric acid (1 to 1.5 times the molar mass of zinc nitrate) are added, and the mixture is stirred until the solid melts. Ammonia water (28% by mass concentration) is added dropwise, and the pH is adjusted to 8.5. The mixture is dried at a constant temperature of 75 to 85°C for 7 to 9 hours to obtain a wet gel. The wet gel is vacuum-dried at 100°C for 7 to 9 hours to obtain a dry gel. The dry gel is calcined at 600°C in a muffle furnace for 3 to 5 hours, and cooled to room temperature to obtain copper / zinc oxide nanoparticles.
[0009] (2) pre-modified copper / zinc oxide nanoparticles, 0.2 mol / L sodium hydroxide solution, and DL-homocysteine thiolactone hydrochloride were mixed and reacted at 35-55°C for 0.5-1.5 h, 3-dimethylaminopropylamine was added, and the reaction was continued for 30 min. The mixture was filtered, and the filter residue was washed with deionized water for 3-5 times and dried in vacuum at 40°C for 5-7 h to obtain modified copper / zinc oxide nanoparticles;
[0010] (3) polysiloxane and pre-polyester were mixed in a mass ratio of (0.5-0.9):20 and added to a reactor, tetrabutyl titanate (0.1% by mass of the pre-polyester) was added, and the temperature was raised to 220° C. for reaction for 30 min under a nitrogen atmosphere, antimony trioxide (0.0001-0.0002 times by mass of the pre-polyester) was added, the temperature was raised to 230° C., vacuum was slowly applied, and the temperature was raised to 265° C. The reaction was continued until the reactants showed a climbing phenomenon, the reaction was terminated, and the material was discharged to obtain a modified polyester;
[0011] (4) The modified polyester and modified copper / zinc oxide nanoparticles are mixed in a mass ratio of 1:(0.01-0.03), melt-extruded using a twin-screw extruder, granulated after extrusion, dried, spun using a melt spinning machine, and stretched using a parallel drawing machine. The obtained fiber is allowed to stand at 85°C for 6 hours to obtain the obtained fiber.
[0012] As an optimization, the preparation method of the pre-modified copper / zinc oxide nanoparticles in step (2) is as follows: 2.3 to 2.7 parts by mass of copper / zinc oxide nanoparticles, 0.5 to 0.9 parts of N,N'-carbonyldiimidazole, and 25 parts of dimethyl sulfoxide are mixed, reacted at 40 to 60°C for 1 to 5 hours, filtered, and the filter residue is washed with acetone for 3 to 5 times and dried at 50°C for 4 hours to obtain the product.
[0013] As an optimization, the pre-modified copper / zinc oxide nanoparticles, 0.2 mol / L sodium hydroxide solution, DL homocysteine thiolactone hydrochloride, and 3-dimethylaminopropylamine in step (2) are respectively calculated by mass: 1.1-1.5 parts of pre-modified copper / zinc oxide nanoparticles, 25 parts of 0.2 mol / L sodium hydroxide solution, 0.6-1.2 parts of DL homocysteine thiolactone hydrochloride, and 0.5 part of 3-dimethylaminopropylamine.
[0014] As an optimization, the preparation method of the prepolyester in step (3) is: 1,3-propylene glycol and dimethyl terephthalate are added to a reactor in a molar ratio of 2.2:1, the temperature is raised until all are melted, tetrabutyl titanate with a mass percentage of 0.15% of dimethyl terephthalate is added, the temperature is raised to 160-170°C and the reaction is carried out for 1 hour, after removing methanol, polytetramethylene ether glycol with a mass percentage of 30% of dimethyl terephthalate and tetrabutyl titanate with a mass percentage of 0.1% of dimethyl terephthalate are added, the temperature is raised to 220°C, and stirring is continued for 30 minutes to obtain the obtained product.
[0015] As an optimization, the polytetramethylene ether glycol is polytetramethylene ether glycol with a molecular weight of 1000.
[0016] As an optimization, the preparation method of the polysiloxane in step (3) is as follows: octamethylcyclotetrasiloxane, 3-chloropropylmethyldimethoxysilane, and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1: (0.3-0.5): (0.01-0.03), nitrogen is passed through for 10-20 minutes, and the mixture is stirred at 95-105° C. for 7-9 hours. Hydroxypropyl silicone oil with a mass of 0.1-0.2 times that of octamethylcyclotetrasiloxane is added, the mixture is heated to 130-140° C. at a rate of 10-20° C. / min and stirred for 40-50 minutes. The mixture is distilled at 0.1-0.3 MPa for 1-2 hours to obtain the obtained product.
[0017] As an optimization, the temperature of the first zone of the twin-screw extruder in step (4) is 255°C, the temperature of the second zone is 255°C, the temperature of the third zone is 260°C, the temperature of the fourth zone is 255°C, and the head temperature is 255°C.
[0018] As an optimization, in step (4), the temperature of the melt spinning machine in zone 1 is 270°C, the temperature of zone 2 is 285°C, the temperature of zone 3 is 283°C, the temperature of zone 4 is 280°C, the number of spinneret holes is 36, and the spinning rate is 600m / min.
[0019] As an optimization, the parallel drawing machine drawing ratio in step (4) is 3.5.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing the skin-friendly antibacterial fiber, the present invention comprises the following steps: reacting zinc nitrate and copper nitrate and then calcining to obtain copper / zinc oxide nanoparticles; activating the copper / zinc oxide nanoparticles with N,N'-carbonyldiimidazole and then reacting them with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to obtain modified copper / zinc oxide nanoparticles; reacting octamethylcyclotetrasiloxane with 3-chloropropylmethyldimethoxysilane and then with hydroxypropyl silicone oil to obtain polysiloxane; reacting 1,3-propylene glycol, dimethyl terephthalate and polytetramethylene ether glycol to obtain prepolyester; reacting the prepolyester with polysiloxane to obtain modified polyester; and melt-extruding the modified polyester and the modified copper / zinc oxide nanoparticles through a twin-screw extruder, granulating and spinning to obtain the fiber.
[0022] First, copper / zinc oxide nanoparticles were activated with N,N'-carbonyldiimidazole and then reacted with DL-homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to produce modified copper / zinc oxide nanoparticles. 3-dimethylaminopropylamine introduced a tertiary amine structure onto the copper / zinc oxide nanoparticles, which reacted with the chloropropyl group on the polysiloxane to form a quaternary ammonium salt. As a cation, the quaternary ammonium salt exhibits excellent antimicrobial properties, thereby effectively improving the antimicrobial properties of the skin-friendly antimicrobial fiber. Furthermore, the quaternary ammonium salt exhibits excellent hydrophilicity, which effectively increases the moisture regain of the skin-friendly antimicrobial fiber. Furthermore, the thiolactone group reacts with 3-dimethylaminopropylamine via an amidolysis ring-opening reaction, resulting in abundant thiol groups on the surface of the modified copper / zinc oxide nanoparticles. As polar groups, thiol groups exhibit excellent hydrophilicity, thereby effectively increasing the moisture regain of the skin-friendly antimicrobial fiber.
[0023] Secondly, copper ions can effectively broaden the bandwidth of zinc oxide, which on the one hand improves the antibacterial activity of zinc oxide, and on the other hand, the antibacterial properties of copper ions themselves can further improve the antibacterial properties. The prepared copper / zinc oxide nanoparticles can effectively play a good antibacterial effect as an antibacterial agent and effectively improve the antibacterial properties. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0025] Example 1:
[0026] A method for preparing skin-friendly antibacterial fiber comprises the following steps:
[0027] (1) Zinc nitrate and copper nitrate were mixed in a molar ratio of 20:1, deionized water 3 times the mass of zinc nitrate and citric acid 1 times the molar number of zinc nitrate were added, and the mixture was stirred until the solid melted. Ammonia water with a mass concentration of 28% was added dropwise, and the pH was adjusted to 8.5. The mixture was dried at a constant temperature of 75°C for 7 hours to obtain a wet gel. The wet gel was vacuum-dried at 100°C for 7 hours to obtain a dry gel. The dry gel was calcined at 600°C in a muffle furnace for 3 hours and cooled to room temperature to obtain copper / zinc oxide nanoparticles.
[0028] (2) 2.3 parts by mass of copper / zinc oxide nanoparticles, 0.5 parts of N,N'-carbonyldiimidazole, and 25 parts of dimethyl sulfoxide were mixed, reacted at 40°C for 1 hour, filtered, and the filter residue was washed with acetone three times and dried at 50°C for 4 hours to obtain pre-modified copper / zinc oxide nanoparticles; 1.1 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts of 0.2 mol / L sodium hydroxide solution, and 0.6 parts of DL-homocysteine thiolactone hydrochloride were reacted at 35°C for 0.5 hour, and then 0.5 parts by mass of 3-dimethylaminopropylamine was added and the reaction was continued for 30 minutes, filtered, and the filter residue was washed with deionized water three times and dried in a vacuum at 40°C for 5 hours to obtain modified copper / zinc oxide nanoparticles;
[0029] (3) Octamethylcyclotetrasiloxane, 3-chloropropylmethyldimethoxysilane, and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.3:0.01, purged with nitrogen for 10 minutes, stirred at 95°C for 7 hours, and 0.1 times the mass of hydroxypropyl silicone oil of octamethylcyclotetrasiloxane was added. The mixture was heated to 130°C at a rate of 10°C / min and stirred for 40 minutes. The mixture was distilled at 0.1 MPa for 1 hour to obtain polysiloxane.
[0030] (4) 1,3-propylene glycol and dimethyl terephthalate were added to the reactor in a molar ratio of 2.2:1, and the temperature was raised until all were melted. Tetrabutyl titanate (0.15% by weight of dimethyl terephthalate) was added, and the temperature was raised to 160°C for 1 hour. After removing the methanol, polytetramethylene ether glycol (30% by weight of dimethyl terephthalate) and tetrabutyl titanate (0.1% by weight of dimethyl terephthalate) were added, and the temperature was raised to 220°C and stirred for 30 minutes. n, preparing a prepolyester; mixing polysiloxane and prepolyester in a mass ratio of 0.5:20 and adding to a reactor, adding 0.1% of tetrabutyl titanate by mass of the prepolyester, heating to 220° C. and reacting for 30 minutes under a nitrogen atmosphere, adding 0.0001 times the mass of the prepolyester by mass of antimony trioxide, heating to 230° C., slowly evacuating, and then heating to 265° C., reacting until the reactants show a climbing phenomenon, terminating the reaction, and discharging the material to obtain a modified polyester;
[0031] (5) The modified polyester and modified copper / zinc oxide nanoparticles were mixed in a mass ratio of 1:0.01, and melt-extruded using a twin-screw extruder. The temperature of the first zone of the twin-screw extruder was 255°C, the temperature of the second zone was 255°C, the temperature of the third zone was 260°C, the temperature of the fourth zone was 255°C, and the temperature of the die head was 255°C. After extrusion, granulation was performed, and drying was performed. The fibers were spun using a melt spinning machine. The temperature of the first zone of the melt spinning machine was 270°C, the temperature of the second zone was 285°C, the temperature of the third zone was 283°C, and the temperature of the fourth zone was 280°C. The number of spinneret holes was 36, the spinning rate was 600 m / min, and the drafting ratio of the parallel drafting machine was 3.5. The obtained fiber was allowed to stand at 85°C for 6 h to obtain the obtained fiber.
[0032] Example 2:
[0033] A method for preparing skin-friendly antibacterial fiber comprises the following steps:
[0034] (1) Zinc nitrate and copper nitrate were mixed in a molar ratio of 20:1, deionized water 4 times the mass of zinc nitrate and citric acid 1.3 times the molar number of zinc nitrate were added, and the mixture was stirred until the solid melted. Ammonia water with a mass concentration of 28% was added dropwise, and the pH was adjusted to 8.5. The mixture was dried at a constant temperature of 80°C for 8 hours to obtain a wet gel. The wet gel was vacuum-dried at 100°C for 8 hours to obtain a dry gel. The dry gel was calcined at 600°C in a muffle furnace for 4 hours and cooled to room temperature to obtain copper / zinc oxide nanoparticles.
[0035] (2) 2.5 parts by weight of copper / zinc oxide nanoparticles, 0.7 parts of N,N'-carbonyldiimidazole, and 25 parts of dimethyl sulfoxide were mixed and reacted at 50°C for 3 hours, filtered, and the filter residue was washed with acetone 4 times and dried at 50°C for 4 hours to obtain pre-modified copper / zinc oxide nanoparticles; 1.3 parts by weight of pre-modified copper / zinc oxide nanoparticles, 25 parts of 0.2 mol / L sodium hydroxide solution, and 0.9 parts of DL-homocysteine thiolactone hydrochloride were reacted at 45°C for 1 hour, and then 0.5 parts by weight of 3-dimethylaminopropylamine were added and the reaction was continued for 30 minutes, filtered, and the filter residue was washed with deionized water 4 times and dried in a vacuum at 40°C for 6 hours to obtain modified copper / zinc oxide nanoparticles;
[0036] (3) Octamethylcyclotetrasiloxane, 3-chloropropylmethyldimethoxysilane, and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.4:0.02, purged with nitrogen for 15 minutes, stirred at 100°C for 8 hours, and 0.15 times the mass of hydroxypropyl silicone oil of octamethylcyclotetrasiloxane was added. The mixture was heated to 135°C at a rate of 15°C / min and stirred for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain polysiloxane.
[0037] (4) 1,3-propylene glycol and dimethyl terephthalate were added to the reactor in a molar ratio of 2.2:1, and the temperature was raised until all were melted. Tetrabutyl titanate (0.15% by weight of dimethyl terephthalate) was added, and the temperature was raised to 165°C for reaction for 1 hour. After removing the methanol, polytetramethylene ether glycol (30% by weight of dimethyl terephthalate) and tetrabutyl titanate (0.1% by weight of dimethyl terephthalate) were added, and the temperature was raised to 220°C and stirred for 30 minutes. , to prepare prepolyester; polysiloxane and prepolyester are mixed in a mass ratio of 0.7:20 and added to a reactor, 0.1% of tetrabutyl titanate by mass of the prepolyester is added, and under a nitrogen atmosphere, the temperature is raised to 220° C. for reaction for 30 minutes, 0.00015 times the mass of the prepolyester by mass of antimony trioxide is added, the temperature is raised to 230° C., vacuum is slowly applied, and the temperature is raised to 265° C., and the reaction is continued until the reactants show a climbing phenomenon, the reaction is terminated, and the material is discharged to prepare a modified polyester;
[0038] (5) The modified polyester and modified copper / zinc oxide nanoparticles were mixed in a mass ratio of 1:0.02, and melt-extruded using a twin-screw extruder. The temperature of the first zone of the twin-screw extruder was 255°C, the temperature of the second zone was 255°C, the temperature of the third zone was 260°C, the temperature of the fourth zone was 255°C, and the temperature of the die head was 255°C. After extrusion, granulation was performed, dried, and spun using a melt spinning machine. The temperature of the first zone of the melt spinning machine was 270°C, the temperature of the second zone was 285°C, the temperature of the third zone was 283°C, and the temperature of the fourth zone was 280°C. The number of spinneret holes was 36, the spinning rate was 600m / min, and the drafting ratio of the parallel drafting machine was 3.5. The obtained fiber was allowed to stand at 85°C for 6h to obtain the obtained fiber.
[0039] Example 3:
[0040] A method for preparing skin-friendly antibacterial fiber comprises the following steps:
[0041] (1) Zinc nitrate and copper nitrate were mixed in a molar ratio of 20:1, deionized water 5 times the mass of zinc nitrate and citric acid 1.5 times the molar number of zinc nitrate were added, and the mixture was stirred until the solid melted. Ammonia water with a mass concentration of 28% was added dropwise, and the pH was adjusted to 8.5. The mixture was dried at a constant temperature of 85°C for 9 hours to obtain a wet gel. The wet gel was vacuum-dried at 100°C for 9 hours to obtain a dry gel. The dry gel was calcined at 600°C in a muffle furnace for 5 hours and cooled to room temperature to obtain copper / zinc oxide nanoparticles.
[0042] (2) 2.7 parts by weight of copper / zinc oxide nanoparticles, 0.9 parts of N,N'-carbonyldiimidazole, and 25 parts of dimethyl sulfoxide were mixed, reacted at 60°C for 5 hours, filtered, and the filter residue was washed with acetone 5 times and dried at 50°C for 4 hours to obtain pre-modified copper / zinc oxide nanoparticles; 1.5 parts by weight of pre-modified copper / zinc oxide nanoparticles, 25 parts of 0.2 mol / L sodium hydroxide solution, and 1.2 parts of DL-homocysteine thiolactone hydrochloride were reacted at 55°C for 1.5 hours, and then 0.5 parts by weight of 3-dimethylaminopropylamine was added, and the reaction was continued for 30 minutes, filtered, and the filter residue was washed with deionized water 5 times and dried in vacuo at 40°C for 7 hours to obtain modified copper / zinc oxide nanoparticles;
[0043] (3) Octamethylcyclotetrasiloxane, 3-chloropropylmethyldimethoxysilane, and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.5:0.03, purged with nitrogen for 20 minutes, stirred at 105°C for 9 hours, and 0.2 times the mass of octamethylcyclotetrasiloxane hydroxypropyl silicone oil was added. The temperature was raised to 140°C at 20°C / min and continued to stir for 50 minutes. The mixture was distilled at 0.3 MPa for 2 hours to obtain polysiloxane.
[0044] (4) 1,3-propylene glycol and dimethyl terephthalate were added to the reactor in a molar ratio of 2.2:1, and the temperature was raised until all were melted. Tetrabutyl titanate (0.15% by weight of dimethyl terephthalate) was added, and the temperature was raised to 170°C for 1 hour. After removing the methanol, polytetramethylene ether glycol (30% by weight of dimethyl terephthalate) and tetrabutyl titanate (0.1% by weight of dimethyl terephthalate) were added, and the temperature was raised to 220°C and stirred for 30 minutes. n, preparing a prepolyester; mixing polysiloxane and prepolyester in a mass ratio of 0.9:20 and adding to a reactor, adding 0.1% of tetrabutyl titanate by mass of the prepolyester, heating to 220° C. and reacting for 30 minutes under a nitrogen atmosphere, adding 0.0002 times the mass of the prepolyester by mass of antimony trioxide, heating to 230° C., slowly evacuating, and then heating to 265° C., reacting until the reactants showed a climbing phenomenon, terminating the reaction, and discharging the material to obtain a modified polyester;
[0045] (5) The modified polyester and modified copper / zinc oxide nanoparticles were mixed in a mass ratio of 1:0.03, and melt-extruded using a twin-screw extruder. The temperature of the first zone of the twin-screw extruder was 255°C, the temperature of the second zone was 255°C, the temperature of the third zone was 260°C, the temperature of the fourth zone was 255°C, and the temperature of the die head was 255°C. After extrusion, granulation was performed, and drying was performed. The fibers were spun using a melt spinning machine. The temperature of the first zone of the melt spinning machine was 270°C, the temperature of the second zone was 285°C, the temperature of the third zone was 283°C, and the temperature of the fourth zone was 280°C. The number of spinneret holes was 36, the spinning rate was 600 m / min, and the drafting ratio of the parallel drafting machine was 3.5. The obtained fiber was allowed to stand at 85°C for 6 h to obtain the obtained fiber.
[0046] Comparative Example 1:
[0047] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.6 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 35°C for 0.5 hour".
[0048] Comparative Example 2:
[0049] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 35°C for 1 hour".
[0050] Comparative Example 3:
[0051] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 1.2 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 35°C for 1.5 hours".
[0052] Comparative Example 4:
[0053] The difference from Example 2 is that step (2) is different, and the step of "taking 1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" is adjusted to "taking 1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 0.5 hour".
[0054] Comparative Example 5:
[0055] The difference from Example 2 is that step (2) is different, and the method of "taking 1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" is adjusted to "taking 1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 1.2 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour".
[0056] Comparative Example 6:
[0057] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.6 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1.5 hours".
[0058] Comparative Example 7:
[0059] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 1.2 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 55°C for 0.5 hour".
[0060] Comparative Example 8:
[0061] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.6 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 55°C for 1 hour".
[0062] Comparative Example 9:
[0063] The difference from Example 2 is that step (2) is different, and the reaction mixture is adjusted from "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 45°C for 1 hour" to "1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts by mass of 0.2 mol / L sodium hydroxide solution, and 0.9 parts by mass of DL homocysteine thiolactone hydrochloride, and reacting at 55°C for 1.5 hours".
[0064] Comparative Example 10:
[0065] Comparative Example 10 differs from Example 2 in that step (2) is modified as follows: 2.5 parts by mass of copper / zinc oxide nanoparticles, 0.7 parts of N,N'-carbonyldiimidazole, and 25 parts of dimethyl sulfoxide are mixed, reacted at 50°C for 3 hours, filtered, and the filter residue is washed four times with acetone and dried at 50°C for 4 hours to obtain pre-modified copper / zinc oxide nanoparticles; 1.3 parts by mass of pre-modified copper / zinc oxide nanoparticles, 25 parts of 0.2 mol / L sodium hydroxide solution, and 0.9 parts of DL-homocysteine thiolactone hydrochloride are reacted at 45°C for 1 hour, and then 0.5 parts by mass of 1-propylamine are added, the reaction is continued for 30 minutes, filtered, the filter residue is washed four times with deionized water, and vacuum-dried at 40°C for 6 hours to obtain modified copper / zinc oxide nanoparticles. The remaining steps are the same as in Example 2.
[0066] Comparative Example 11:
[0067] Comparative Example 11 differs from Example 2 in that steps (1) and (2) are not performed, and step (5) is modified as follows: the modified polyester is melt-extruded using a twin-screw extruder, the temperature of the first zone of the twin-screw extruder is 255°C, the temperature of the second zone is 255°C, the temperature of the third zone is 260°C, the temperature of the fourth zone is 255°C, and the head temperature is 255°C. After extrusion, the modified polyester is pelletized and dried. The modified polyester is spun using a melt spinning machine, the temperature of the first zone of the melt spinning machine is 270°C, the temperature of the second zone is 285°C, the temperature of the third zone is 283°C, and the temperature of the fourth zone is 280°C. The number of spinneret holes is 36, the spinning rate is 600 m / min, and the drafting ratio of the parallel drafting machine is 3.5. The obtained fiber is allowed to stand at 85°C for 6 hours to obtain the obtained fiber. The remaining steps are the same as those in Example 2.
[0068] Comparative Example 12:
[0069] Comparative Example 12 differs from Example 2 in that step (2) is omitted and step (5) is modified as follows: the modified polyester and copper / zinc oxide nanoparticles are mixed in a mass ratio of 1:(0.01-0.03), melt-extruded using a twin-screw extruder, the temperature of the first zone of the twin-screw extruder is 255°C, the temperature of the second zone is 255°C, the temperature of the third zone is 260°C, the temperature of the fourth zone is 255°C, and the head temperature is 255°C. After extrusion, granulation is performed, drying is performed, and spinning is performed using a melt spinning machine, the temperature of the first zone of the melt spinning machine is 270°C, the temperature of the second zone is 285°C, the temperature of the third zone is 283°C, and the temperature of the fourth zone is 280°C, the number of spinneret holes is 36, the spinning rate is 600 m / min, the draft ratio of the parallel drafting machine is 3.5, and the obtained fiber is allowed to stand at 85°C for 6 hours to obtain the fiber. The remaining steps are the same as those in Example 2.
[0070] Test Example 1:
[0071] Thiol content testing of modified copper / zinc oxide nanoparticles: 0.025 g of modified copper / zinc oxide nanoparticles was added to 2 mL of 5 mmol tris(2-carboxyethyl)phosphine hydrochloride in phosphate buffer (pH 7.4) and allowed to soak for 1 hour to completely remove double bonds. After the reaction, the particles were rinsed three times with Ellman's reaction buffer. 2 mL of Ellman's reagent was added and allowed to react at room temperature for 15 minutes. The particles were then diluted to 10 mL with Ellman's reaction buffer and the absorbance at 412 nm was measured using a spectrophotometer to determine the thiol content. The results are shown in Table 1.
[0072] Table 1
[0073]
[0074] From the orthogonal test data comparison of Comparative Examples 1 to 9 in Table 1, it can be found that the optimal reaction conditions are a reaction temperature of 35° C., a reaction time of 1 h, and a mass fraction of DL homocysteine thiolactone hydrochloride of 0.9 parts.
[0075] Copper / zinc oxide nanoparticles activated with N,N'-carbonyldiimidazole reacted with DL-homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to produce modified copper / zinc oxide nanoparticles. The surface hydroxyl content of the copper / zinc oxide nanoparticles was constant, as was the content of ester imidazole produced after activation with N,N'-carbonyldiimidazole. Once the ester imidazole had completely reacted, further increasing the amount of DL-homocysteine thiolactone hydrochloride failed to further increase the surface thiol content. Therefore, the optimal amount of DL-homocysteine thiolactone hydrochloride was 0.9 parts by weight. Increasing the reaction temperature accelerated molecular motion and increased the probability of intermolecular collisions, favoring the reaction. However, as the reaction temperature increased, the content of byproducts increased, hindering the probability of collisions between DL-homocysteine thiolactone hydrochloride and ester imidazole. After the reaction reached equilibrium, further increasing the temperature had little effect on the surface thiol content of the modified copper / zinc oxide nanoparticles. Because the active sites on the surface of copper / zinc oxide nanoparticles are limited after activation with N,N'-carbonyldiimidazole, when the ester imidazole is completely reacted, the thiol content on the surface of copper / zinc oxide nanoparticles will not continue to increase if the reaction time is extended. Therefore, the optimal reaction time is 1h.
[0076] Test Example 2:
[0077] Antibacterial Performance Test: The skin-friendly antibacterial fibers prepared in the Examples and Comparative Examples were tested using the Quine test method to determine their antibacterial rates against Staphylococcus aureus. The results are shown in Table 2.
[0078] Table 2
[0079] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.7 Comparative Example 10 89.1 Example 2 99.8 Comparative Example 11 8.7 Example 3 99.8 Comparative Example 12 88.4
[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 10 to 12 in Table 2, it can be found that the skin-friendly antibacterial fiber prepared in the present invention has good antibacterial properties.
[0081] By comparison, the antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 10, indicating that copper / zinc oxide nanoparticles are activated by N, N'-carbonyldiimidazole and reacted with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to prepare modified copper / zinc oxide nanoparticles. 3-dimethylaminopropylamine introduces a tertiary amine structure on the copper / zinc oxide nanoparticles, which reacts with the chloropropyl group on the polysiloxane to form a quaternary ammonium salt. The quaternary ammonium salt has good antibacterial properties as a cation, thereby effectively improving the antibacterial properties of the skin-friendly antibacterial fiber. The antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 11, indicating that copper ions can effectively broaden the bandwidth of zinc oxide, on the one hand, improving the antibacterial performance of the skin-friendly antibacterial fiber. The antibacterial activity of zinc oxide is improved. On the one hand, the antibacterial property of copper ions themselves can further improve the antibacterial property. The prepared copper / zinc oxide nanoparticles can effectively play a good antibacterial effect as an antibacterial agent, and effectively improve the antibacterial property. The antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 12, indicating that the copper / zinc oxide nanoparticles are activated by N,N'-carbonyldiimidazole and reacted with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to prepare modified copper / zinc oxide nanoparticles. 3-dimethylaminopropylamine introduces a tertiary amine structure on the copper / zinc oxide nanoparticles, which reacts with the chloropropyl group on the polysiloxane to form a quaternary ammonium salt. The quaternary ammonium salt has good antibacterial properties as a cation.
[0082] Test Example 3:
[0083] Moisture regain test: Moisture regain test was conducted on the examples and comparative examples according to GB / T6503-2017 "Test method for moisture regain of chemical fibers". The results are shown in Table 3.
[0084] Table 3
[0085] Moisture regain Moisture regain Example 1 4.59% Comparative Example 10 3.26% Example 2 4.63% Comparative Example 11 3.03% Example 3 4.52% Comparative Example 12 2.57%
[0086] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 10 to 12 in Table 3, it can be found that the skin-friendly antibacterial fiber prepared in the present invention has good moisture absorption performance.
[0087] By comparison, the moisture regains of Examples 1 to 3 are greater than that of Comparative Example 10, indicating that 3-dimethylaminopropylamine introduces a tertiary amine structure on the copper / zinc oxide nanoparticles, and reacts with the chloropropyl group on the polysiloxane to form a quaternary ammonium salt. The quaternary ammonium salt has good hydrophilicity and effectively improves the moisture regain by improving the hydrophilicity of the skin-friendly antibacterial fiber; the moisture regains of Examples 1 to 3 are greater than that of Comparative Example 11, indicating that the copper / zinc oxide nanoparticles are activated by N, N'-carbonyldiimidazole and reacted with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to prepare modified copper / zinc oxide nanoparticles, and the thiolactone group undergoes an aminolysis ring-opening reaction with 3-dimethylaminopropylamine, so that the surface of the modified copper / zinc oxide nanoparticles has abundant thiol groups, and the thiol groups act as It is a polar group with good hydrophilicity, thereby effectively improving the moisture regain of the skin-friendly antibacterial fiber; the moisture regains of Examples 1 to 3 are greater than that of Comparative Example 12, indicating that 3-dimethylaminopropylamine introduces a tertiary amine structure on the copper / zinc oxide nanoparticles, and reacts with the chloropropyl group on the polysiloxane to form a quaternary ammonium salt. After the copper / zinc oxide nanoparticles are activated by N,N'-carbonyldiimidazole, they react with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine to prepare modified copper / zinc oxide nanoparticles. The thiolactone group undergoes an aminolysis ring-opening reaction with 3-dimethylaminopropylamine, so that the surface of the modified copper / zinc oxide nanoparticles has abundant thiol groups. Both the quaternary ammonium salt and the thiol group have good hydrophilicity, which can effectively improve the moisture regain of the skin-friendly antibacterial fiber.
[0088] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A skin-friendly antibacterial fiber, characterized in that: The skin-friendly antibacterial fiber is prepared by melt-extruding modified polyester and modified copper / zinc oxide nanoparticles through a twin-screw extruder, granulating, and spinning; The modified polyester is prepared by reacting octamethylcyclotetrasiloxane with 3-chloropropylmethyldimethoxysilane and then reacting with hydroxypropyl silicone oil to prepare polysiloxane, and reacting 1,3-propylene glycol, dimethyl terephthalate, and polytetramethylene ether glycol to prepare pre-polyester and then reacting with polysiloxane; The modified copper / zinc oxide nanoparticles are prepared by reacting zinc nitrate and copper nitrate and then calcining the resulting copper / zinc oxide nanoparticles, which are activated by N,N'-carbonyldiimidazole and then reacted with DL homocysteine thiolactone hydrochloride and 3-dimethylaminopropylamine.
2. A method for preparing skin-friendly antibacterial fiber, characterized in that: The method comprises the following preparation steps: (1) zinc nitrate and copper nitrate are mixed in a molar ratio of 20:1, deionized water (3 to 5 times the mass of zinc nitrate) and citric acid (1 to 1.5 times the molar mass of zinc nitrate) are added, and the mixture is stirred until the solid melts. Ammonia water (28% by mass concentration) is added dropwise, and the pH is adjusted to 8.
5. The mixture is dried at a constant temperature of 75 to 85°C for 7 to 9 hours to obtain a wet gel. The wet gel is vacuum-dried at 100°C for 7 to 9 hours to obtain a dry gel. The dry gel is calcined at 600°C in a muffle furnace for 3 to 5 hours, and cooled to room temperature to obtain copper / zinc oxide nanoparticles. (2) pre-modified copper / zinc oxide nanoparticles, 0.2 mol / L sodium hydroxide solution, and DL-homocysteine thiolactone hydrochloride were mixed and reacted at 35-55°C for 0.5-1.5 h, 3-dimethylaminopropylamine was added, and the reaction was continued for 30 min. The mixture was filtered, and the filter residue was washed with deionized water for 3-5 times and dried in vacuum at 40°C for 5-7 h to obtain modified copper / zinc oxide nanoparticles; (3) polysiloxane and pre-polyester were mixed in a mass ratio of (0.5-0.9):20 and added to a reactor, tetrabutyl titanate (0.1% by mass of the pre-polyester) was added, and the temperature was raised to 220° C. for reaction for 30 min under a nitrogen atmosphere, antimony trioxide (0.0001-0.0002 times by mass of the pre-polyester) was added, the temperature was raised to 230° C., vacuum was slowly applied, and the temperature was raised to 265° C. The reaction was continued until the reactants showed a climbing phenomenon, the reaction was terminated, and the material was discharged to obtain a modified polyester; (4) The modified polyester and modified copper / zinc oxide nanoparticles are mixed in a mass ratio of 1:(0.01-0.03), melt-extruded using a twin-screw extruder, granulated after extrusion, dried, spun using a melt spinning machine, and stretched using a parallel drawing machine. The obtained fiber is allowed to stand at 85°C for 6 hours to obtain the obtained fiber.
3. The method for preparing a skin-friendly antibacterial fiber according to claim 2, characterized in that: The preparation method of the pre-modified copper / zinc oxide nanoparticles in step (2) is as follows: 2.3 to 2.7 parts by mass of copper / zinc oxide nanoparticles, 0.5 to 0.9 parts of N,N'-carbonyldiimidazole, and 25 parts of dimethyl sulfoxide are mixed, reacted at 40 to 60°C for 1 to 5 hours, filtered, and the filter residue is washed with acetone for 3 to 5 times and dried at 50°C for 4 hours to obtain the product.
4. The method for preparing a skin-friendly antibacterial fiber according to claim 2, characterized in that: The pre-modified copper / zinc oxide nanoparticles, 0.2 mol / L sodium hydroxide solution, DL homocysteine thiolactone hydrochloride, and 3-dimethylaminopropylamine in step (2) are respectively calculated by mass: 1.1-1.5 parts of pre-modified copper / zinc oxide nanoparticles, 25 parts of 0.2 mol / L sodium hydroxide solution, 0.6-1.2 parts of DL homocysteine thiolactone hydrochloride, and 0.5 part of 3-dimethylaminopropylamine.
5. The method for preparing a skin-friendly antibacterial fiber according to claim 2, characterized in that: The preparation method of the prepolyester in step (3) is as follows: 1,3-propylene glycol and dimethyl terephthalate are added to a reactor in a molar ratio of 2.2:1, the temperature is raised until all are melted, tetrabutyl titanate with a mass fraction of 0.15% of the mass of dimethyl terephthalate is added, the temperature is raised to 160-170° C. and the reaction is carried out for 1 hour. After removing methanol, polytetramethylene ether glycol with a mass fraction of 30% of the mass of dimethyl terephthalate and tetrabutyl titanate with a mass fraction of 0.1% of the mass of dimethyl terephthalate are added, the temperature is raised to 220° C., and stirring is continued for 30 minutes to obtain the prepolyester.
6. The method for preparing a skin-friendly antibacterial fiber according to claim 5, characterized in that: The polytetramethylene ether glycol is a polytetramethylene ether glycol with a molecular weight of 1000.
7. The method for preparing a skin-friendly antibacterial fiber according to claim 2, characterized in that: The preparation method of the polysiloxane in step (3) is as follows: octamethylcyclotetrasiloxane, 3-chloropropylmethyldimethoxysilane, and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1: (0.3-0.5): (0.01-0.03), nitrogen is passed through for 10-20 minutes, and the mixture is stirred at 95-105° C. for 7-9 hours. Hydroxypropyl silicone oil with a mass of 0.1-0.2 times that of octamethylcyclotetrasiloxane is added, the mixture is heated to 130-140° C. at a rate of 10-20° C. / min and stirred for 40-50 minutes. The mixture is distilled at 0.1-0.3 MPa for 1-2 hours to obtain the polysiloxane.
8. The method for preparing a skin-friendly antibacterial fiber according to claim 2, characterized in that: In step (4), the temperature of zone 1 of the twin-screw extruder is 255°C, the temperature of zone 2 is 255°C, the temperature of zone 3 is 260°C, the temperature of zone 4 is 255°C, and the head temperature is 255°C.
9. The method for preparing a skin-friendly antibacterial fiber according to claim 2, characterized in that: In step (4), the temperature of the melt spinning machine zone 1 is 270°C, the temperature of the zone 2 is 285°C, the temperature of the zone 3 is 283°C, the temperature of the zone 4 is 280°C, the number of spinneret holes is 36, and the spinning rate is 600m / min.
10. The method for preparing skin-friendly antibacterial fiber according to claim 2, characterized in that: The parallel drawing machine in step (4) has a drawing multiple of 3.5.